Augmented reality-guided online shopping mobile application - Shim, Wei En (2022)
People's behaviour improved with these intelligent technologies and covid-19 pandemic to get rid of old traditions that limit society and even human beings by restricted under the lockdown policy. Meanwhile, the biggest drawback facing is the ability to touch, feel and try products, and the fact that the products consumers receive often do not match the description as it generally adopting text and pictures approach. Thus, a more detailed and realistic visualization of the product is lacking in existing mobile commerce applications. Those description might be a great test of human comprehension as varying individual comprehension and intelligibility on different product. Therefore, this project is implementing Augmented Reality function to help consumers, and it was proven to increase sales conversions. There is a web application for administrators to manage and a mobile application for consumers. The requirements of the application be analysed through literature review and existing applications with user needs and usage intent. The adopted methodology in this project is Prototyping-based Methodology. The augmented reality function implemented by ViroReact visualize GL Transmission Format Binary file(GLB) models about a physical object in the real world and there is 10 specific product models were proposed, all of which were built by blender. This project uses a three-tier architecture, application, server, and database. Firebase is the database and node.js is used for server-side scripting. The results show that the augmented reality features are helpful for the product description, but more features are recommended to enrich the mobile application.